Chloroplast pH Homeostasis for the Regulation of Photosynthesis - Trinh, Mai Duy Luu; Masuda, Shinji (Frontiers in Plant Science, 2022)
The pH of various chloroplast compartments, such as the thylakoid lumen and stroma, are light-dependent. Light illumination induces electron transfer in the photosynthetic apparatus, coupled with proton translocation across the thylakoid membranes, resulting in acidification and alkalization of the thylakoid lumen and stroma, respectively. Luminal acidification is crucial for inducing regulatory mechanisms that protect photosystems against photodamage caused by the overproduction of reactive oxygen species (ROS). Stromal alkalization activates enzymes involved in the Calvin-Benson-Bassham (CBB) cycle. Moreover, proton translocation across the thylakoid membranes generates a proton gradient (pH) and an electric potential (), both of which comprise the proton motive force (pmf) that drives ATP synthase. Then, the synthesized ATP is consumed in the CBB cycle and other chloroplast metabolic pathways. In the dark, the pH of both the chloroplast stroma and thylakoid lumen becomes neutral. Despite extensive studies of the above-mentioned processes, the molecular mechanisms of how chloroplast pH can be maintained at proper levels during the light phase for efficient activation of photosynthesis and other metabolic pathways and return to neutral levels during the dark phase remain largely unclear, especially, in terms of the precise control of stromal pH. The transient increase and decrease in chloroplast pH upon dark-to-light and light-to-dark transitions have been considered as signals for controlling other biological processes in plant cells. Forward and reverse genetic screening approaches recently identified new plastid proteins involved in controlling pH and  across the thylakoid membranes and chloroplast proton/ion homeostasis. These proteins have been conserved during the evolution of oxygenic phototrophs and include putative photosynthetic protein complexes, proton transporters, and/or their regulators. Herein, we summarize the recently identified protein players that control chloroplast pH and influence photosynthetic efficiency in plants.